Mobile Health Treatment Support Intervention for HIV and Tuberculosis in Mozambique Perspectives of Patients and Healthcare Workers: A Literature Review - Damon Wicaksi (Universitas Bondowoso, 2020)
Introduction: Tuberculosis (TB) and HIV / AIDS are two major diseases that are the focus of public health. TB and HIV can each cause death due to infection, if TB accompanies AIDS it can cause the death of one in three patients with AIDS, in Mozambique 1.5 million people were infected with HIV/AIDS and 223 new patients were infected and 108 died due to HIV per day. Method: The critical appraisal tool used in the discussion of this journal is CASP (Critical Appraisal Skill Program). In this study, using RCTs involving 404 TB and HIV patients. However, the journal does not explain how to take it randomly. Result: Most of the patients (HIV 82% [56/68], TB 97% [65/67]) reported that they did not skip their drug collection at any time. This is consistent with the medication collection rates recorded in the patient database (78% and 94%, respectively) The experimental and control groups received the same treatment. This is shown in the journal in the discussion chapter which states that this study found that retention of antiretroviral therapy was very good in the control and intervention groups (91% vs 94%). Conclusion: Research results from this journal can be used as input and as material for reflection for health workers that currently the challenge faced by health workers is the creation of innovations related to interventions in the community.